Effects of climate change on coastal fresh groundwater resources - Sarukkalige, Priyantha Ranjan; Kazama, S.; Sawamoto, M. (Elsevier, 2006)
This study evaluates the impacts of climate change on fresh groundwater resources specifically salinity intrusion in water resources stressed coastal aquifers. Our assessment used the Hadley Centre climate model, HadCM3 with high and low emission scenarios (SRES A2 and B2) for years 2000-2099. In both scenarios, the annual fresh groundwater resources losses indicate an increasing long-term trend in all stressed areas, except in the northern Africa/Sahara region. We also found that precipitation and temperature individually did not show good correlations with fresh groundwater loss. However, the relationship between the aridity index and fresh groundwater loss exhibited a strong negative correlation. We also discuss the impacts of loss of fresh groundwater resources on socio-economic activities, mainly population growth and per capita fresh groundwater resources.